Preparation method and application of asymmetric charged covalent organic framework composite cellulose acetate nanofiltration membrane

By introducing non-uniformly distributed charged COF nanosheets into cellulose acetate membranes, asymmetric charged structures are constructed, and the problems of non-renewable and low desalting efficiency of existing nanofiltration membrane materials are solved, and efficient industrial wastewater and seawater are achieved Desalination treatment.

CN119258813AActive Publication Date: 2025-01-07FUJIAN AGRI & FORESTRY UNIV
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411564880.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-05
Publication Date
2025-01-07
Estimated Expiration
2044-11-05

Smart Images

  • Figure CN119258813A_ABST
    Figure CN119258813A_ABST
Patent Text Reader

Abstract

The invention relates to an asymmetric charged covalent organic framework composite cellulose acetate nanofiltration membrane as well as a preparation method and application thereof. The preparation method comprises the following steps: dispersing COF nanosheets in DMF, adding acetone and cellulose acetate to prepare a membrane casting solution, stirring, defoaming, pre-volatilizing for corresponding time by using a blade coating method, and carrying out phase inversion in deionized water to form the membrane. According to the invention, a surface segregation technology is adopted, and a non-uniformly distributed charge structure is constructed in a film by using a COF material with high charge density. The obtained asymmetric charged covalent organic framework composite cellulose acetate nanofiltration membrane is applied to ion nanofiltration, has better performance, can realize nanofiltration desalination, and has great prospects in the industries of seawater desalination, wastewater treatment and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of chemical utilization of cellulose acetate, and specifically relates to an asymmetric charged covalent organic framework composite cellulose acetate nanofiltration membrane and a preparation method and application thereof. Background Art

[0002] Nanofiltration is a membrane separation technology with a precision between ultrafiltration and reverse osmosis. Under pressure, the nanofiltration membrane only allows water molecules to pass through efficiently while high-valent salt ions are retained. At present, ion nanofiltration technology is mainly used in the following aspects: 1) Wastewater purification. Industrial and municipal wastewater has a high salt content, and direct discharge will cause serious environmental pollution and waste. Removing high-valent salt ions through nanofiltration has become an efficient water treatment process. 2) Ion resource utilization. With the rapid development of new energy and other industries, the demand for lithium has increased dramatically. Separating lithium ions from impurity ions through nanofiltration technology has become a low-energy, low-cost, green and environmentally friendly lithium extraction strategy and has received widespread attention. The pore size of the nanofiltration membrane is between that of the ultrafiltration membrane and the reverse osmosis membrane (0.5-2nm), and solute retention can be achieved through the steric hindrance effect. The nanofiltration membrane can also achieve desalination through the electrostatic effect, that is, the electrostatic effect between the charged pores and ions interferes with ion transfer and thus affects the desalination performance. At present, nanofiltration technology is mainly based on non-renewable petroleum-based polymer membrane materials, which are difficult to degrade and pose challenges to the sustainability of the entire life cycle. Cellulose acetate (CA) is a bio-based membrane material based on natural cellulose and has been widely used in the preparation of commercial reverse osmosis membranes. However, its efficiency in nanofiltration desalination is poor because its charge is lower than that of existing polyamide nanofiltration membranes and its electrostatic desalination effect is weak.

[0003] Inspired by the charged structure of the roots of salt-tolerant mangrove plants, this study proposed the concept of asymmetric charged nanofiltration membranes, introduced non-uniformly distributed charged groups into the cellulose acetate membrane, strengthened the role of electrostatic effect in the nanofiltration desalination process, and achieved size screening coupled electrostatic desalination. Ionic covalent organic frameworks (iCOFs) are a new class of crystalline charged polymer materials that can provide highly ordered one-dimensional charged nanochannels. Taking sulfonic acid covalent organic frameworks (NUS-9 and NUS-10) as an example, the charge density of their mass transfer channels is as high as hundreds of mC / m 2 , far exceeding the artificial charged channels and biological charged channels reported so far, and is an ideal charged nanoelement. This project introduces charged COF nanosheets during the phase transformation of cellulose acetate, realizes the non-uniform distribution of COF in the membrane through surface segregation technology, constructs an asymmetric charged cellulose acetate nanofiltration membrane, strengthens the charge density on the membrane surface, and improves the ion nanofiltration performance through the surface electrostatic effect and coordinated size screening mechanism. Expand the application of COF materials and biomass materials in the field of high-tech, but related results are rarely reported. Summary of the invention

[0004] The purpose of the present invention is to overcome the above-mentioned defects and provide a method for preparing an asymmetric charged covalent organic framework composite cellulose acetate nanofiltration membrane, wherein COF nanosheets are dispersed in DMF, acetone and cellulose acetate are added to prepare a casting solution, and after stirring and degassing, a scraping method is used, and then pre-volatilization for a corresponding time is performed, and a phase conversion is performed in deionized water to form a membrane. The surface segregation technology is used to construct a non-uniformly distributed charged structure in the membrane with a high charge density COF material. By adjusting the amount of COF added and changing the pre-volatilization time, the thresholds of different parameters are determined to obtain a nanofiltration membrane with the best performance for nanofiltration desalination.

[0005] To achieve the above object, the present invention adopts the following technical solution:

[0006] First, the COF nanosheets were dispersed in DMF, and then acetone and cellulose acetate (the volume ratio of DMF: acetone was 1:2, and the mass fraction of cellulose acetate was 20wt%) were added to prepare a casting solution, which was magnetically stirred at room temperature for 12 hours and allowed to stand for degassing for 24 hours. The casting solution was scraped on a glass plate, pre-evaporated for 0min, 1min, 1.5min, and 2min, respectively, and then placed in deionized water for phase transformation into a membrane. The obtained membrane was cross-linked with a glutaraldehyde solution, rinsed and stored in deionized water. The obtained asymmetric covalent organic framework composite cellulose acetate membrane was used for ion nanofiltration, which can achieve desalination of industrial wastewater, seawater, brackish water, etc.

[0007] Furthermore, the COF nanosheet is a sulfonated COF nanosheet NUS-9, which is prepared by liquid-liquid interfacial polymerization.

[0008] In step 1, the mass fraction of COF in the casting solution is 0.005wt%-0.05wt%.

[0009] In step 1, the amount of COF added is preferably 1 mg.

[0010] In step 2, the pre-volatilization time is preferably 1 min.

[0011] In step 3, the concentration of the cross-linking glutaraldehyde solution is 4 wt %, the temperature is set at 60° C., and the duration is 20 min.

[0012] Compared with the prior art, the present invention has the following advantages:

[0013] (1) The present invention proposes a method for constructing an asymmetric structure of COF in a membrane, and uses surface segregation technology to prepare an asymmetric charged covalent organic framework composite cellulose acetate nanofiltration membrane with a membrane thickness of micrometer order;

[0014] (2) The asymmetric charged covalent organic framework composite cellulose acetate nanofiltration membrane prepared by the present invention has a special structure that can improve the permeability while increasing the retention rate, and exhibits excellent performance in the field of ion nanofiltration desalination.

[0015] (3) The present invention uses DMF as a solvent, which can not only make the COF nanosheets dispersed evenly, but also work together with acetone to dissolve cellulose acetate, providing a new idea for the solvent selection of COF composite cellulose acetate membrane. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 This is a scanning electron microscope (SEM) image of the COF nanosheets used.

[0017] Figure 2 This is a cross-sectional electron microscope (SEM) image of the asymmetric charged covalent organic framework composite cellulose acetate nanofiltration membrane prepared in Example 6.

[0018] Figure 3 This is the EDX-mapping-N element image of the asymmetric charged covalent organic framework composite cellulose acetate nanofiltration membrane prepared in Example 6.

[0019] Figure 4 This is the retention of high concentration sodium sulfate (1000 ppm, 2000 ppm, 3000 ppm, 4000 ppm) solutions by the asymmetric charged covalent organic framework composite cellulose acetate nanofiltration membrane prepared in Example 6.

[0020] Figure 5 The retention of six salts, namely sodium sulfate, magnesium sulfate, magnesium chloride, potassium chloride, lithium chloride and sodium chloride, by the asymmetric charged covalent organic framework composite cellulose acetate nanofiltration membrane prepared in Examples 5-8. DETAILED DESCRIPTION

[0021] The present invention is further described below by specific embodiments and drawings. The embodiments of the present invention are intended to enable those skilled in the art to better understand the present invention, and do not limit the present invention in any way.

[0022] The COF nanosheets used in the following examples are sulfonated COF nanosheets NUS-9, which are prepared by liquid-liquid interfacial polymerization. The specific preparation method is based on the preparation of IPC-COF in the literature: Cao L, Wu H, Cao Y, et al. Weaklyhumidity-dependent proton-conducting COF membranes [J]. Advanced Materials, 2020, 32 (52): 2005565.

[0023] Example 1: Preparation of asymmetric charged covalent organic framework composite cellulose acetate membrane-1, the steps are as follows:

[0024] Step 1: Weigh 0.5 mg COF and disperse it in 2.67 ml DMF, then add acetone and cellulose acetate (the volume ratio of DMF:acetone is 1:2, and the mass fraction of cellulose acetate is 20 wt%) to prepare a casting solution. The SEM image of the COF nanosheets used is as follows: Figure 1 .

[0025] Step 2: Stir magnetically at room temperature for 12 hours and let stand to degas for 24 hours.

[0026] Step 3: Scrape the casting solution onto a glass plate, pre-evaporate for 0 min, and then place it in deionized water for phase conversion to form a film.

[0027] Step 4: The prepared membrane is cross-linked with a 4 wt % glutaraldehyde solution, rinsed and stored in deionized water.

[0028] The obtained asymmetric charged COF composite cellulose acetate nanofiltration membrane-1 was then used for nanofiltration of six salts, namely sodium sulfate, magnesium sulfate, magnesium chloride, potassium chloride, lithium chloride, and sodium chloride.

[0029] The rejection rate of the asymmetric charged COF composite cellulose acetate membrane-1 prepared in Example 1 for sodium sulfate (1000 ppm) solution was 75.28%.

[0030] The rejection rate of the asymmetric charged COF composite cellulose acetate membrane-1 prepared in Example 1 for magnesium sulfate (1000 ppm) solution was 74.21%.

[0031] The rejection rate of the asymmetric charged COF composite cellulose acetate membrane-1 prepared in Example 1 for magnesium chloride (1000 ppm) solution was 74.88%.

[0032] The rejection rate of the asymmetric charged COF composite cellulose acetate membrane-1 prepared in Example 1 for potassium chloride (1000 ppm) solution was 68.60%.

[0033] The rejection rate of the asymmetric charged COF composite cellulose acetate membrane-1 prepared in Example 1 for lithium chloride (1000 ppm) solution was 66.13%.

[0034] The rejection rate of the asymmetric charged COF composite cellulose acetate membrane-1 prepared in Example 1 for sodium chloride (1000 ppm) solution was 62.31%.

[0035] Example 2: Preparation of asymmetric charged covalent organic framework composite cellulose acetate membrane-2. The preparation process is basically the same as that of Example 1, except that the pre-volatilization time in step 3 is changed to 1 min to obtain asymmetric charged COF composite cellulose acetate membrane-2.

[0036] The obtained asymmetric charged COF composite cellulose acetate nanofiltration membrane-2 was then used for nanofiltration of six salts, namely sodium sulfate, magnesium sulfate, magnesium chloride, potassium chloride, lithium chloride, and sodium chloride.

[0037] The rejection rate of the asymmetric charged COF composite cellulose acetate membrane-1 prepared in Example 2 for sodium sulfate (1000 ppm) solution was 84.95%.

[0038] The rejection rate of the asymmetric charged COF composite cellulose acetate membrane-1 prepared in Example 2 for magnesium sulfate (1000 ppm) solution was 82.81%.

[0039] The rejection rate of the asymmetric charged COF composite cellulose acetate membrane-1 prepared in Example 2 for magnesium chloride (1000 ppm) solution was 78.89%.

[0040] The rejection rate of the asymmetric charged COF composite cellulose acetate membrane-1 prepared in Example 2 for potassium chloride (1000 ppm) solution was 68.77%.

[0041] The rejection rate of the asymmetric charged COF composite cellulose acetate membrane-1 prepared in Example 2 for lithium chloride (1000 ppm) solution was 64.16%.

[0042] The rejection rate of the asymmetric charged COF composite cellulose acetate membrane-1 prepared in Example 2 for sodium chloride (1000 ppm) solution was 66.28%.

[0043] Example 3: Preparation of asymmetric charged covalent organic framework composite cellulose acetate membrane-3. The preparation process is basically the same as that of Example 1, except that the pre-volatilization time in step three is changed to 1.5 min to obtain asymmetric charged COF composite cellulose acetate membrane-3.

[0044] The obtained asymmetric charged COF composite cellulose acetate nanofiltration membrane-3 was then used for nanofiltration of six salts, namely sodium sulfate, magnesium sulfate, magnesium chloride, potassium chloride, lithium chloride, and sodium chloride.

[0045] The rejection rate of the asymmetric charged COF composite cellulose acetate membrane-3 prepared in Example 3 for sodium sulfate (1000 ppm) solution was 54.26%.

[0046] The rejection rate of the asymmetric charged COF composite cellulose acetate membrane-3 prepared in Example 3 for magnesium sulfate (1000 ppm) solution was 50.54%.

[0047] The rejection rate of the asymmetric charged COF composite cellulose acetate membrane-3 prepared in Example 3 for magnesium chloride (1000 ppm) solution was 45.03%.

[0048] The rejection rate of the asymmetric charged COF composite cellulose acetate membrane-3 prepared in Example 3 for potassium chloride (1000 ppm) solution is 38.35%.

[0049] The rejection rate of the asymmetric charged COF composite cellulose acetate membrane-3 prepared in Example 3 for lithium chloride (1000 ppm) solution is 38.90%.

[0050] The rejection rate of the asymmetric charged COF composite cellulose acetate membrane-3 prepared in Example 3 for sodium chloride (1000 ppm) solution is 32.72%.

[0051] Example 4: Preparation of asymmetric charged covalent organic framework composite cellulose acetate membrane-4. The preparation process is basically the same as that of Example 1, except that the pre-volatilization time in step 3 is changed to 2 minutes to obtain asymmetric charged COF composite cellulose acetate membrane-4.

[0052] The obtained asymmetric charged COF composite cellulose acetate nanofiltration membrane-4 was then used for nanofiltration of six salts, namely sodium sulfate, magnesium sulfate, magnesium chloride, potassium chloride, lithium chloride, and sodium chloride.

[0053] The rejection rate of the asymmetric charged COF composite cellulose acetate membrane-4 prepared in Example 4 for sodium sulfate (1000 ppm) solution was 39.37%.

[0054] The rejection rate of the asymmetric charged COF composite cellulose acetate membrane-4 prepared in Example 4 for magnesium sulfate (1000 ppm) solution was 35.53%.

[0055] The rejection rate of the asymmetric charged COF composite cellulose acetate membrane-4 prepared in Example 4 for magnesium chloride (1000 ppm) solution was 26.57%.

[0056] The rejection rate of the asymmetric charged COF composite cellulose acetate membrane-4 prepared in Example 4 for potassium chloride (1000 ppm) solution was 21.03%.

[0057] The rejection rate of the asymmetric charged COF composite cellulose acetate membrane-4 prepared in Example 4 for lithium chloride (1000 ppm) solution was 24.72%.

[0058] The rejection rate of the asymmetric charged COF composite cellulose acetate membrane-4 prepared in Example 4 for sodium chloride (1000 ppm) solution was 22.89%.

[0059] Example 5: Preparation of asymmetric charged covalent organic framework composite cellulose acetate membrane-5. The preparation process is basically the same as that of Example 1, except that the amount of COF added in step 1 is changed to 1 mg to obtain asymmetric charged COF composite cellulose acetate membrane-5.

[0060] The obtained asymmetric charged COF composite cellulose acetate nanofiltration membrane-5 was then used for nanofiltration of six salts, namely sodium sulfate, magnesium sulfate, magnesium chloride, potassium chloride, lithium chloride, and sodium chloride.

[0061] The rejection rate of the asymmetric charged COF composite cellulose acetate membrane-5 prepared in Example 5 for sodium sulfate (1000 ppm) solution was 73.52%.

[0062] The rejection rate of the asymmetric charged COF composite cellulose acetate membrane-5 prepared in Example 5 for magnesium sulfate (1000 ppm) solution was 78.50%.

[0063] The rejection rate of the asymmetric charged COF composite cellulose acetate membrane-5 prepared in Example 5 for magnesium chloride (1000 ppm) solution was 78.47%.

[0064] The rejection rate of the asymmetric charged COF composite cellulose acetate membrane-5 prepared in Example 5 for potassium chloride (1000 ppm) solution was 62.11%.

[0065] The rejection rate of the asymmetric charged COF composite cellulose acetate membrane-5 prepared in Example 5 for lithium chloride (1000 ppm) solution is 66.93%.

[0066] The rejection rate of the asymmetric charged COF composite cellulose acetate membrane-5 prepared in Example 5 for sodium chloride (1000 ppm) solution is 62.82%.

[0067] Example 6: Preparation of asymmetric charged covalent organic framework composite cellulose acetate membrane-6. The preparation process is basically the same as that of Example 1, except that the amount of COF added in step 1 is changed to 1 mg; the pre-volatilization time in step 3 is changed to 1 min, and an asymmetric charged COF composite cellulose acetate membrane-6 is obtained. The cross-sectional electron micrograph of the asymmetric charged COF composite cellulose acetate nanofiltration membrane-6 is shown in FIG. Figure 2 As shown, the cross-section EDX-mapping-N elements are as follows Figure 3 shown.

[0068] The obtained asymmetric charged COF composite cellulose acetate nanofiltration membrane-6 was then used for nanofiltration of six salts, namely sodium sulfate, magnesium sulfate, magnesium chloride, potassium chloride, lithium chloride, and sodium chloride.

[0069] The rejection rate of the asymmetric charged COF composite cellulose acetate membrane-6 prepared in Example 6 for sodium sulfate (1000 ppm) solution was 93.59%.

[0070] The rejection rate of the asymmetric charged COF composite cellulose acetate membrane-6 prepared in Example 6 for magnesium sulfate (1000 ppm) solution was 92.09%.

[0071] The rejection rate of the asymmetric charged COF composite cellulose acetate membrane-6 prepared in Example 6 for magnesium chloride (1000 ppm) solution was 90.57%.

[0072] The rejection rate of the asymmetric charged COF composite cellulose acetate membrane-6 prepared in Example 6 for potassium chloride (1000 ppm) solution was 74.98%.

[0073] The rejection rate of the asymmetric charged COF composite cellulose acetate membrane-6 prepared in Example 6 for lithium chloride (1000 ppm) solution is 74.87%.

[0074] The rejection rate of the asymmetric charged COF composite cellulose acetate membrane-6 prepared in Example 6 for sodium chloride (1000 ppm) solution was 74.52%.

[0075] The retention rates of the asymmetric charged COF composite cellulose acetate membrane-6 prepared in Example 6 for high concentration sodium sulfate solutions (1000ppm, 2000ppm, 3000ppm, 4000ppm) were 93.59%, 87.78%, 86.59%, and 82.46%, respectively. Figure 4 shown.

[0076] Example 7: Preparation of asymmetric charged covalent organic framework composite cellulose acetate membrane-7. The preparation process is basically the same as that of Example 1, except that: in step one, the COF addition amount is changed to 1 mg; in step three, the pre-volatilization time is changed to 1.5 min, to obtain asymmetric charged COF composite cellulose acetate membrane-7.

[0077] The obtained asymmetric charged COF composite cellulose acetate nanofiltration membrane-7 was then used for nanofiltration of six salts, namely sodium sulfate, magnesium sulfate, magnesium chloride, potassium chloride, lithium chloride, and sodium chloride.

[0078] The rejection rate of the asymmetric charged COF composite cellulose acetate membrane-7 prepared in Example 7 for sodium sulfate (1000 ppm) solution was 51.08%.

[0079] The rejection rate of the asymmetric charged COF composite cellulose acetate membrane-7 prepared in Example 7 for magnesium sulfate (1000 ppm) solution was 51.94%.

[0080] The rejection rate of the asymmetric charged COF composite cellulose acetate membrane-7 prepared in Example 7 for magnesium chloride (1000 ppm) solution is 45.79%.

[0081] The rejection rate of the asymmetric charged COF composite cellulose acetate membrane-7 prepared in Example 7 for potassium chloride (1000 ppm) solution is 40.02%.

[0082] The rejection rate of the asymmetric charged COF composite cellulose acetate membrane-7 prepared in Example 7 for lithium chloride (1000 ppm) solution is 41.17%.

[0083] The rejection rate of the asymmetric charged COF composite cellulose acetate membrane-7 prepared in Example 7 for sodium chloride (1000 ppm) solution was 39.28%.

[0084] Example 8: Preparation of asymmetric charged covalent organic framework composite cellulose acetate membrane-8. The preparation process is basically the same as that of Example 1, except that the COF addition amount in step one is changed to 1 mg; the pre-volatilization time in step three is changed to 2 min, thereby obtaining an asymmetric charged COF composite cellulose acetate membrane-8.

[0085] The obtained asymmetric charged COF composite cellulose acetate nanofiltration membrane-8 was then used for nanofiltration of six salts, namely sodium sulfate, magnesium sulfate, magnesium chloride, potassium chloride, lithium chloride, and sodium chloride.

[0086] The rejection rate of the asymmetric charged COF composite cellulose acetate membrane-8 prepared in Example 8 for sodium sulfate (1000 ppm) solution was 28.21%.

[0087] The rejection rate of the asymmetric charged COF composite cellulose acetate membrane-8 prepared in Example 8 for magnesium sulfate (1000 ppm) solution was 25.67%.

[0088] The rejection rate of the asymmetric charged COF composite cellulose acetate membrane-8 prepared in Example 8 for magnesium chloride (1000 ppm) solution was 28.16%.

[0089] The rejection rate of the asymmetric charged COF composite cellulose acetate membrane-8 prepared in Example 8 for potassium chloride (1000 ppm) solution was 24.43%.

[0090] The rejection rate of the asymmetric charged COF composite cellulose acetate membrane-8 prepared in Example 8 for lithium chloride (1000 ppm) solution is 21.56%.

[0091] The rejection rate of the asymmetric charged COF composite cellulose acetate membrane-8 prepared in Example 8 for sodium chloride (1000 ppm) solution was 23.06%.

[0092] Figure 5 This is a graph showing the retention rate changes of the asymmetric charged covalent organic framework composite cellulose acetate membrane 5-8 for six salts, namely, sodium sulfate, magnesium sulfate, magnesium chloride, potassium chloride, lithium chloride, and sodium chloride (1000 ppm).

[0093] Example 9: Preparation of asymmetric charged covalent organic framework composite cellulose acetate membrane-9. The preparation process is basically the same as that of Example 1, except that the amount of COF added in step 1 is changed to 2 mg to obtain asymmetric charged COF composite cellulose acetate membrane-9.

[0094] The obtained asymmetric charged COF composite cellulose acetate nanofiltration membrane-9 was then used for nanofiltration of six salts, namely sodium sulfate, magnesium sulfate, magnesium chloride, potassium chloride, lithium chloride, and sodium chloride.

[0095] The rejection rate of the asymmetric charged COF composite cellulose acetate membrane-9 prepared in Example 9 for sodium sulfate (1000 ppm) solution was 71.39%.

[0096] The rejection rate of the asymmetric charged COF composite cellulose acetate membrane-9 prepared in Example 9 for magnesium sulfate (1000 ppm) solution was 69.12%.

[0097] The rejection rate of the asymmetric charged COF composite cellulose acetate membrane-9 prepared in Example 9 for magnesium chloride (1000 ppm) solution was 70.52%.

[0098] The rejection rate of the asymmetric charged COF composite cellulose acetate membrane-9 prepared in Example 9 for potassium chloride (1000 ppm) solution was 54.35%.

[0099] The rejection rate of the asymmetric charged COF composite cellulose acetate membrane-9 prepared in Example 9 for lithium chloride (1000 ppm) solution was 63.35%.

[0100] The rejection rate of the asymmetric charged COF composite cellulose acetate membrane-9 prepared in Example 9 for sodium chloride (1000 ppm) solution was 57.40%.

[0101] Example 10: Preparation of asymmetric charged covalent organic framework composite cellulose acetate membrane-10. The preparation process is basically the same as that of Example 1, except that the COF addition amount in step one is changed to 2 mg; the pre-volatilization time in step three is changed to 1 min, thereby obtaining an asymmetric charged COF composite cellulose acetate membrane-10.

[0102] The obtained asymmetric charged COF composite cellulose acetate nanofiltration membrane-10 was then used for nanofiltration of six salts, namely sodium sulfate, magnesium sulfate, magnesium chloride, potassium chloride, lithium chloride, and sodium chloride.

[0103] The rejection rate of the asymmetric charged COF composite cellulose acetate membrane-10 prepared in Example 10 for sodium sulfate (1000 ppm) solution was 76.72%.

[0104] The rejection rate of the asymmetric charged COF composite cellulose acetate membrane-10 prepared in Example 10 for magnesium sulfate (1000 ppm) solution was 75.95%.

[0105] The rejection rate of the asymmetric charged COF composite cellulose acetate membrane-10 prepared in Example 10 for magnesium chloride (1000 ppm) solution was 75.36%.

[0106] The rejection rate of the asymmetric charged COF composite cellulose acetate membrane-10 prepared in Example 10 for potassium chloride (1000 ppm) solution was 63.78%.

[0107] The rejection rate of the asymmetric charged COF composite cellulose acetate membrane-10 prepared in Example 10 for lithium chloride (1000 ppm) solution was 62.46%.

[0108] The rejection rate of the asymmetric charged COF composite cellulose acetate membrane-10 prepared in Example 10 for sodium chloride (1000 ppm) solution was 62.51%.

[0109] Example 11, preparation of asymmetric charged covalent organic framework composite cellulose acetate membrane-11, the preparation process is basically the same as that of Example 1, the only difference is: in step one, the COF addition amount is changed to 2 mg; in step three, the pre-volatilization time is changed to 1.5 min, to obtain asymmetric charged COF composite cellulose acetate membrane-11.

[0110] The obtained asymmetric charged COF composite cellulose acetate nanofiltration membrane-11 was then used for nanofiltration of six salts, namely sodium sulfate, magnesium sulfate, magnesium chloride, potassium chloride, lithium chloride, and sodium chloride.

[0111] The rejection rate of the asymmetric charged COF composite cellulose acetate membrane-11 prepared in Example 11 for sodium sulfate (1000 ppm) solution was 59.08%.

[0112] The rejection rate of the asymmetric charged COF composite cellulose acetate membrane-11 prepared in Example 11 for magnesium sulfate (1000 ppm) solution was 57.42%.

[0113] The rejection rate of the asymmetric charged COF composite cellulose acetate membrane-11 prepared in Example 11 for magnesium chloride (1000 ppm) solution was 46.90%.

[0114] The rejection rate of the asymmetric charged COF composite cellulose acetate membrane-11 prepared in Example 11 for potassium chloride (1000 ppm) solution was 44.01%.

[0115] The rejection rate of the asymmetric charged COF composite cellulose acetate membrane-11 prepared in Example 11 for lithium chloride (1000 ppm) solution was 37.62%.

[0116] The rejection rate of the asymmetric charged COF composite cellulose acetate membrane-11 prepared in Example 11 for sodium chloride (1000 ppm) solution was 40.21%.

[0117] Example 12: Preparation of asymmetric charged covalent organic framework composite cellulose acetate membrane-12. The preparation process is basically the same as that of Example 1, except that: in step one, the COF addition amount is changed to 2 mg; in step three, the pre-volatilization time is changed to 2 min, to obtain asymmetric charged COF composite cellulose acetate membrane-12.

[0118] The obtained asymmetric charged COF composite cellulose acetate nanofiltration membrane-12 was then used for nanofiltration of six salts, namely sodium sulfate, magnesium sulfate, magnesium chloride, potassium chloride, lithium chloride, and sodium chloride.

[0119] The rejection rate of the asymmetric charged COF composite cellulose acetate membrane-12 prepared in Example 12 for sodium sulfate (1000 ppm) solution was 40.98%.

[0120] The rejection rate of the asymmetric charged COF composite cellulose acetate membrane-12 prepared in Example 12 for magnesium sulfate (1000 ppm) solution was 36.70%.

[0121] The rejection rate of the asymmetric charged COF composite cellulose acetate membrane-12 prepared in Example 12 for magnesium chloride (1000 ppm) solution was 32.57%.

[0122] The retention rate of the asymmetric charged COF composite cellulose acetate membrane-12 prepared in Example 12 for potassium chloride (1000 ppm) solution was 30.99%.

[0123] The rejection rate of the asymmetric charged COF composite cellulose acetate membrane-12 prepared in Example 12 for lithium chloride (1000 ppm) solution is 26.83%.

[0124] The rejection rate of the asymmetric charged COF composite cellulose acetate membrane-12 prepared in Example 12 for sodium chloride (1000 ppm) solution was 27.25%.

[0125] The comparison of the retention performance of the membranes prepared in various embodiments of the present invention for six kinds of salts is shown in Table 1:

[0126] Table 1

[0127]

[0128]

[0129] Through the above-mentioned embodiments, the present invention has obtained corresponding experimental results.

[0130] According to the data in Table 1, it can be seen that: in the preparation process of the asymmetric charged COF composite cellulose acetate membrane of the present invention, 1. the change of the pre-volatilization time can affect the asymmetric charged structure of the membrane. With the increase of time, the water permeability increases accordingly, and the interception increases first and then decreases. There is a threshold value for the effect of the pre-volatilization time on the membrane structure; 2. It can be seen from Examples 1, 5, and 9 that the change of the COF addition amount can change the charge of the asymmetric charged membrane, thereby strengthening the electrostatic effect of the nanofiltration process. With the increase of the COF addition amount, the water permeability and the interception rate of the six salts increase first and then decrease as a whole; 3. The formation of an asymmetric charged structure can not only improve the water permeability, but also improve the interception rate of each salt. The best performance of the asymmetric charged COF composite cellulose acetate membrane is Example 6, and the interception performance of the six salts reaches the highest, among which sodium sulfate>magnesium sulfate>magnesium chloride>potassium chloride>lithium chloride>sodium chloride.

[0131] Depend on Figure 1 It can be seen that the COF nanosheets added to each membrane have regular shapes and sizes in the single-digit micrometer range, which is conducive to the construction of an asymmetric charged structure.

[0132] Depend on Figure 2 and Figure 3 It can be seen that in Example 6, the casting solution was pre-evaporated for 1 minute after being scraped, and an asymmetric physical structure was constructed. The COF nanosheets formed a charge enrichment layer on the upper part of the membrane through the surface segregation technology, thereby forming a complete and continuous asymmetric charged structure. The membrane has a smooth and flat surface morphology and a thickness of about 120 microns. In addition, Figure 3 It can be seen that the characteristic element of COF, N element, is enriched in the upper part of the membrane, confirming the successful construction of the asymmetric charged COF composite cellulose acetate membrane.

[0133] Depend on Figure 4 It can be seen that the retention rate is stable as the sodium sulfate concentration increases, and the retention rate of 4000 ppm sodium sulfate can reach a maximum of 86.87%.

[0134] Depend on Figure 5 It can be seen that the asymmetric charged COF composite cellulose acetate membranes prepared in Examples 5-8 were tested for the retention of six common salts (1000ppm). The results showed that the retention of the six salts was different, among which sodium sulfate>magnesium sulfate>magnesium chloride>potassium chloride>lithium chloride>sodium chloride. The membrane performance of Example 6 was the best, and the retention rate of sodium sulfate could reach up to 95.41%.

[0135] It should be understood that the implementation schemes and examples discussed here are for illustrative purposes only and may be modified or altered by those skilled in the art, and all such modifications and alterations should fall within the scope of protection of the appended claims of the present invention.

Claims

1. A method for preparing an asymmetric charged covalent organic framework composite cellulose acetate nanofiltration membrane, characterized in that: First, the COF nanosheets were dissolved in N,N-dimethylformamide, and then acetone and cellulose acetate were added to prepare a casting solution. The solution was magnetically stirred at room temperature for 12 hours, and allowed to stand for degassing for 24 hours. The solution was then scraped and pre-evaporated for a corresponding period of time to form an asymmetric charged structure. The solution was then placed in deionized water and phase-transformed into a membrane. The membrane was cross-linked with glutaraldehyde solution for 20 minutes and stored in deionized water.

2. The method for preparing an asymmetric charged covalent organic framework composite cellulose acetate nanofiltration membrane according to claim 1, characterized in that: The COF nanosheet is a sulfonated COF nanosheet NUS-9.

3. The method for preparing the asymmetric charged covalent organic framework composite cellulose acetate nanofiltration membrane according to claim 1, characterized in that: The cellulose acetate has an acetyl content of 39.8 wt % and a hydroxyl content of 3.5 wt %.

4. The method for preparing an asymmetric charged covalent organic framework composite cellulose acetate nanofiltration membrane according to claim 1, characterized in that: The mass fraction of cellulose acetate in the casting solution is 20wt%.

5. The method for preparing an asymmetric charged covalent organic framework composite cellulose acetate nanofiltration membrane according to claim 1, characterized in that: The volume ratio of N,N-dimethylformamide and acetone is 1:

2.

6. The method for preparing an asymmetric charged covalent organic framework composite cellulose acetate nanofiltration membrane according to claim 1, characterized in that: The mass fraction of COF in the casting solution is 0.005wt%-0.05wt%.

7. The method for preparing an asymmetric charged covalent organic framework composite cellulose acetate nanofiltration membrane according to claim 1, characterized in that: The pre-volatilization times are 0 min, 1 min, 1.5 min, and 2 min, respectively.

8. The method for preparing an asymmetric charged covalent organic framework composite cellulose acetate nanofiltration membrane according to claim 1, characterized in that: In the cross-linking process, the concentration of the glutaraldehyde solution is 4 wt %, the temperature is 60° C., and the time is 20 min.

9. An asymmetric charged covalent organic framework composite cellulose acetate nanofiltration membrane prepared according to the preparation method according to any one of claims 1 to 8.

10. The asymmetric charged covalent organic framework composite cellulose acetate nanofiltration membrane according to claim 9 is used for nanofiltration desalination of seawater, wastewater or brackish water.

Citation Information

Patent Citations

  • Cellulose acetate nanofiltration membrane and preparing method thereof

    CN105327623A

  • Functionally gradient covalent organic framework membrane as well as preparation and application

    CN107970790A

  • Forward osmosis membrane based on TPB-DMTP-COF as well as preparation method and application of forward osmosis membrane

    CN118512929A

  • Carboxymethyl-beta-cyclodextrin modified covalent organic framework nanosheet / aramid nanofiber composite nanofiltration membrane and preparation method thereof

    CN118831454A

  • Method, system and non-transitory computer-readable recording medium for transaction of goods

    KR1020230108195A